(untitled) (Journal of Health Sciences, 2021)
Introduction: Autologous platelet-rich plasma (PRP) has been a growing trend in the field of medicine due to its broad range of application and is considered safe from bloodborne diseases. Furthermore, various studies have tried to optimize the use of autologous PRP through various preparation protocols, including PRP activation. However, most of the studies available have not evaluated the safety for intravenous delivery of PRP, especially autologous activated PRP (aaPRP). Therefore, this study aimed to evaluate the safety of intravenous delivery of aaPRP.Methods: Blood was drawn from each patient and aaPRP was isolated through calcium activation and light irradiation. Each aaPRP was administered intravenously to all patients. Adverse events were documented and analyzed.Results: Six hundred eleven patients participated in this study with a total of 4244 aaPRP therapies. Quality control of autologous aaPRP showed no platelets present after both calcium activation and light irradiation. No adverse events such as allergic reaction, infection, and coagulation problems were observed on all patients over the course of the study.Conclusion: Our results showed that intravenous administration of autologous aaPRP is safe even in patients with various pathological conditions.